An annotated catalog of the Iranian Pentatomoidea (Hemiptera: Heteroptera: Pentatomomorpha) - Ghahari, Hassan; Moulet, Pierre; Rider, David A. (Zootaxa, 2014)
Seven families of Pentatomoidea including Acanthosomatidae, Dinidoridae, Pentatomidae, Plataspididae, Scutelleridae, Thaumastellidae, and Thyreocoridae are discussed in this catalog. The Iranian fauna of Pentatomoidea (excl. Cydnidae) is represented by 99 genera and 271 species and subspecies. Elasmostethus interstinctus (Linnaeus, 1758) (Acanthosomatidae) and Derula flavoguttata Mulsant & Rey, 1856 (Pentatomidae) are new records for Iran.